2020
DOI: 10.3390/genes11101155
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling Analyses in Psoriasis: A Dynamic Contribution of Keratinocytes to the Pathogenesis

Abstract: Psoriasis is an immune-mediated inflammatory skin disease with a complex etiology involving environmental and genetic factors. A better insight into related genomic alteration helps design precise therapies leading to better treatment outcome. Gene expression in psoriasis can provide relevant information about the altered expression of mRNA transcripts, thus giving new insights into the disease onset. Techniques for transcriptome analyses, such as microarray and RNA sequencing (RNA-seq), are relevant tools for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 126 publications
1
17
0
Order By: Relevance
“…There is also a localized overexpression of IFI27 and PI3 in the suprabasal layer. Some of these results complement previous findings obtained by bulk microarray, GWAS, and NGS methods [56,59,74,75]. Such examples include the AD-like loss of differentiation signature from the top epidermal layers (FLG, LOR, KRT10, KRT1) and a loss of expression of genes involved in lipid metabolism (EVOLV3, FABP5) [74].…”
Section: Psoriasissupporting
confidence: 82%
“…There is also a localized overexpression of IFI27 and PI3 in the suprabasal layer. Some of these results complement previous findings obtained by bulk microarray, GWAS, and NGS methods [56,59,74,75]. Such examples include the AD-like loss of differentiation signature from the top epidermal layers (FLG, LOR, KRT10, KRT1) and a loss of expression of genes involved in lipid metabolism (EVOLV3, FABP5) [74].…”
Section: Psoriasissupporting
confidence: 82%
“…The transcriptome of psoriasis skin has been extensively explored and compared with both non-lesional skin and skin from healthy controls [ 24 , 25 , 26 ], but not much attention has been drawn to the blood transcriptome in psoriasis. Recently, however, blood transcriptomic profiling of patients with psoriasis vs. controls identified inflammasome signaling as the most upregulated canonical pathway in psoriasis and found a common gene transcript signature related to neutrophil-driven inflammation [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two opposite biological processes (herbivorous diet leading to GPR15–C10ORF99 signalling and colonic Treg homing, and no herbivorous diet over a long time period, leading to the loss of colonic C10ORF99 expression) suggested that colonic Treg homing reactions can be promoted by an herbivorous diet, but can be disrupted by the lack of an herbivorous diet over a long time period, leading to disappearance of the colon and the loss of a functional C10ORF99 gene. In addition, the mRNA expression of C10ORF99 was also induced in skin in response to epithelial damage and TLR signalling (Kiene et al , 2014 ; Rioux et al , 2020 ), and is highly upregulated in skin during inflammatory diseases such as psoriasis (Suply et al , 2017 ; Chen et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%